Comparative study between the surgical mangement of reinke's edema with microdebrider and conventional surgery - ابراهيم , مصطفى; علي , ياسر; حمدان , هبا (Latakia University Journal -Medical Sciences Series, 2021)
Objectives : Microdebride is a new technology in management of reinke's edema is. The aim of our study is to Compare between the use of traditional endoscopic laryngeal instruments and "Microdebrider" device in surgical treatment of reinke;s edema. Material and Methods: 60 patients with reinke's edema (48 females and 12 males) underwent endoscopic surgery, divided into two groups: Group 1 ( 25 patients underwent surgery using traditional surgical instruments ) , Group 2 ( 35 patients with microdebrider was). Results were evaluated during surgery and a month later. Results : We found consistent improvement in all parameters both in conventional instruments and microdebrider group. The parameters were statistically better after microdebrider surgery. Duration of surgery is lower (t test < t score : a = 0.05) , and bleeding is less when using microdebrider (calculated z < z theory: a = 0.05). There is no significant difference between two groups in terms of recurrent and improvement of voice after one month . But adhesions rate after a month of surgery is lower when using a microdebrider. Conclusions: Microdebrider is a safe and effective device in management of reinke's edema. The oscillatory cutting knife and low suction protect lamina propria resulting in better vibratory function. It saves time of surgery , reduces bleeding and decreases the following adhesions .